Food, Talk, and Knitting - Jocelyn Ahlers (Semiotic Review)
Language socialization, the process by which individuals acquire identity markers associated with particular communities of practice, continues throughout life (Ochs 2000; Garrett and Baquedano-Lopez 2002); food often plays an important role creating environments where socialization can take place (e.g. Ochs and Shohet 2006). This paper considers the process by which some people, while learning to knit, are also socialized into identity as “knitter”, a process marked and facilitated by shared food consumption. Examining data gathered through participant-observation within two knitting groups, coupled with data drawn from a large on-line survey of the knitting community at large, I argue that food and language are mutually constitutive of the socialization experience for knitters, not simply due to co-occurrence, but because they indirectly index ideologies which underpin different knitting identities; that is, knitting and food are both semiotic resources in the expression of broader identities which have ideological and social coherence. Among some groups of knitters, this is a broader identity of service, sacrifice, and community building; among others, it is an identity associated with values of self-expression and feminism.